Postoperative Infection After Cesarean Section: Can Timing of Antibiotics Administration Be a Remedy? - Asumah, Mubarick Nungbaso; Abubakari, Abdulai; Mohammed, Abdul-Samed (Cerrahpaşa Medical Journal, 2022)
Cite this article as: Asumah MN, Abubakari A, Mohammed A. Postoperative infection after cesarean section: Can timing of antibiotics administration be a remedy? Cerrahpaşa Med J. 2022;46(3):278-279.